Psychometric properties of the EQ-5D-5L compared with EQ-5D-3L in cancer patients in Iran - Moradi, Nasrin; Poder, Thomas G.; Safari, Hossein; Mojahedian, Mohammad M.; Ameri, Hosein (Frontiers in Oncology, 2022)
Background and Objective Psychometric evidence to support the validity and reliability of the EuroQol-5 Dimensions (EQ-5D) in cancer patients is limited. This study aimed to test the validity and reliability of the EQ-5D-5L (5L) in comparison with EQ-5D-3L (3L) in cancer patients. Methods Data of 650 cancer patients were collected through consecutive sampling method from three largest governmental cancer centers in Iran between June 2021 and January 2022. The data were gathered using the 3L, 5L, and the European Organization for Research and Treatment of Cancer quality of life questionnaire (QLQ-C30) instruments. The 3L and 5L were compared in terms of ceiling effect, discriminatory power, convergent and known-groups validity, relative efficiency, inconsistency, agreement, and reliability. Results Compared with the 3L, ceiling effect decreased by 27.86%. Absolute and relative informativity of discriminatory power improved by 45.93% and 22.92% in the 5L, respectively. All convergent validity coefficients with 5L were stronger than with 3L. Both 3L and 5L demonstrated good known-groups validity, and the relative efficiency was higher for 5L in 4 out of 7 patients’ characteristics. The two instruments showed low overall inconsistency (1.45%) and 92.57% of the differences of observations between the 3L and 5L were within the 95% limit of agreement. The interclass correlation coefficient (ICC) for 3L and 5L indexes were 0.88 and 0.85, respectively, and kappa coefficients in the 3L dimensions (range=0.66-0.92) were higher than the 5L(range=0.64-0.79). Conclusions The 5L demonstrated to be better than the 3L in terms of ceiling effect, inconsistency, discriminatory power, convergent validity, relative efficiency.